Efek Pupuk Daun Bayfolan Terhadap Produktivitas Tanaman Kangkung Darat (Ipomea reptans Poir) - Lismaini (AGRISUSTAIN : Journal of Agribusiness and Sustainable Agriculture, 2025)
The low productivity and quality of land spinach, particularly in Lampung, are due to several factors: the lack of use of superior varieties, limited fertilizer use, inappropriate planting distances, and poor cultivation techniques. One alternative to increasing kale yields is through intensification, which involves the use of fertilizer in the correct dosage and method. This study aims to determine the effect of Bayfolan foliar fertilizer on the productivity of water spinach (Ipomoea reptans Poir). The hypothesis proposed in this study is: the application of foliar fertilizer affects the productivity of water spinach plants, and a dose of 3 ml is the best concentration in increasing the productivity of land spinach (Ipomoea reptans Poir). This study was conducted from December 2024 to February 2025, in Natar, Natar District, South Lampung Regency. The experiment used a completely randomized block design (RAKL) with 5 treatments and 5 replications. The treatments consisted of B0 (without leaf fertilizer), B1 (leaf fertilizer 1 ml/l water), B2 (leaf fertilizer 2 ml/l water), B3 (leaf fertilizer 3 ml/l water), B4 (leaf fertilizer 4 ml/l water). The similarity of data variance was tested using the Bartlett test and the additionality of data was tested using the Tukey test, the data was processed using analysis of variance and the difference in mean values ​​was tested using the BNJ test at the 5% level. Based on the results of the study, it can be concluded: the provision of leaf fertilizer has a significant effect on the productivity of land spinach, and the concentration of 3 ml/l leaf fertilizer has the best effect on the productivity of land spinach plants, especially on the parameters of plant height, number of leaves, leaf length, leaf width, stem diameter, and yield per plot of land spinach plants.